Agriophyllum Oligosaccharides Ameliorate Diabetic Insulin Resistance Through INS-R/IRS/Glut4-Mediated Insulin Pathway in db/db Mice and MIN6 Cells - Bao, Shuyin; Wang, Xiuzhi; Cho, Sung Bo; Wu, Yan-Ling; Wei, Chengxi; Han, Shuying; Bao, Liming; Wu, Qiong; Ao, Wuliji; Nan, Ji-Xing (Frontiers in Pharmacology, 2021)
We have previously reported that Agriophyllum oligosaccharides (AOS) significantly enhance glycemic control by increasing the activation of insulin receptor (INS-R), insulin receptor substrate-2 (IRS-2), phosphatidylinositol 3 kinase (PI3K), protein kinase B (AKT), peroxisome proliferator-activated receptor (PPAR)-γ, and glucose transporter 4 (Glut4) proteins in hepatic tissues. However, the effect of glucose control by AOS on the regulation of pancreatic tissues in db/db mice and MIN6 cells remains to be determined. An oral dose of AOS (380 or 750 mg/kg) was administered to type-2 diabetic db/db mice for 8 weeks to determine whether AOS regulates glucose by the INS-R/IRS/Glut4-mediated insulin pathway. Meanwhile, the effects of AOS on glucose uptake and its related signaling pathway in MIN6 cells were also investigated. The results showed that the random blood glucose (RBG) level in the AOS-treated group was lower than that in the control group. AOS reduced the levels of glycated hemoglobin (HbA1c) and free fatty acid (FFA), and significantly improved the pathological changes in the pancreatic tissues in db/db mice. Moreover, immunohistochemical analysis revealed that the expression of INS-R, IRS-1, IRS-2, and Glut4 was increased in the AOS-treated group than in the model group Further, in vitro experiments using MIN6 cells showed that AOS regulated INS-R, IRS-1, IRS-2, and Glut4 protein and mRNA levels and attenuated insulin resistance and cell apoptosis. The results of both in vitro and in vivo experiments were comparable. Ultra-performance liquid chromatography coupled with time-of-flight mass spectrometric analysis of AOS with pre-column derivatization with 3-amino-9-ethylcarbazole (AEC) tentatively identified five types of sugars: glucose, lactose, rutinose, glucuronic acid, and maltotriose. Our present study clearly showed that AOS is efficacious in preventing hyperglycemia, possibly by increasing insulin sensitivity and improving IR by regulating the INS-R/IRS/Glut4 insulin signal pathway. So AOS may be a potential drug for diabetic treatment.